2018
DOI: 10.1186/s40677-018-0107-3
|View full text |Cite
|
Sign up to set email alerts
|

Individuals’ perceptions of areas exposed to coastal flooding in four French coastal municipalities: the contribution of sketch mapping

Abstract: Background: This study analyzes individuals' perceptions of areas exposed to coastal flooding at a local level using sketch mapping methodology. In this way, 318 individuals were surveyed in four coastal municipalities in France (Barneville-Carteret, Saintes-Maries-de-lamer , Châtelaillon-Plage and Sainte-Anne). We assessed the disagreement between expert estimates and individuals' perceptions of areas exposed to coastal flooding using sketch mapping indicators. We also determined the relationships between ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
0
7
1
Order By: Relevance
“…Our results therefore highlight relatively good local knowledge of the effects of climate change, contrary to some other studies, which identified a gap between experts' and residents' perceptions (Lata and Nunn, 2012;Coquet et al, 2018). The fact that very few tourists or seasonal Fig.…”
Section: Climate Change Perceptions Depend On Environmental Awareness and Knowledge Of The Territorycontrasting
confidence: 65%
See 1 more Smart Citation
“…Our results therefore highlight relatively good local knowledge of the effects of climate change, contrary to some other studies, which identified a gap between experts' and residents' perceptions (Lata and Nunn, 2012;Coquet et al, 2018). The fact that very few tourists or seasonal Fig.…”
Section: Climate Change Perceptions Depend On Environmental Awareness and Knowledge Of The Territorycontrasting
confidence: 65%
“…It may cause a shock or sudden awareness: the person then is more interested in one particular solution than in the others (Lawrence et al, 2014;Thistlethwaite et al, 2018). Secondly, the place of residence near the sea or notmay influence the way the risk is perceived as theoretical or real, and therefore affect the degree of acceptance of adaptation measures (O'Neill et al, 2016;Coquet et al, 2018). Thirdly, cultural capital plays a role in acceptance: the better-educated people are and the better their professional position, the more they may accept intermediate or soft solutions, taxes and restrictive regulations [Appendix E].…”
Section: Social Acceptance Of Adaptation Depends On Place Attachment Experience Of Natural Hazards and Socio-demographic Characteristicsmentioning
confidence: 99%
“…Accurate and successful disaster management paves way for the faster recovery from an uncertain disaster event (Horney et al 2016;Coquet et al 2018). Faster disaster recovery time period depends upon several factors including the management at SME level as well as the government level.…”
Section: Disaster Recovery Time Periodmentioning
confidence: 99%
“…Dongus et al 2007), and environmental hazards (e.g. Coquet, Mercier, and Fleury-Bahi 2018;Klonner et al 2018;O'Neill et al 2015;Sletto et al 2010).…”
Section: Sketch Mappingmentioning
confidence: 99%